Comparison of Lumbar Lordosis in Lateral Radiographs in Standing Position with supine MR Imaging in consideration of the Sacral Slope - Benditz, Achim; Boluki, Daniel; Weber, Markus; Zeman, Florian; Grifka, Joachim; Völlner, Florian (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose To investigate the influence of sacral slope on the correlation between measurements of lumbar lordosis obtained by standing radiographs and magnetic resonance images in supine position (MRI). Little information is available on the correlation between measurements of lumbar lordosis obtained by radiographic and MR images. Most relevant studies have shown correlations for the thoracic spine, but detailed analyses on the lumbar spine are lacking.Methods MR images and standing lateral radiographs of 63 patients without actual low back pain or radiographic pathologies of the lumbar spine were analyzed. Standing radiographic measurements included the sagittal parameters pelvic incidence (PI) pelvic tilt (PT), and sacral slope (SS); MR images were used to additionally measure lumbar L1-S1 lordosis and single level lordosis. Differences between radiographic and MRI measurements were analyzed and divided into 4 subgroups of different sacral slope according to Roussouly’s classification.Results Global lumbar lordosis (L1-S1) was 44.99° (± 10 754) on radiographs and 47.91° (± 9.170) on MRI, yielding a clinically relevant correlation (r = 0.61, p < 0.01). Measurements of single level lordosis only showed minor differences. At all levels except for L5 / S1, lordosis measured by means of standing radiographs was higher than that measured by MRI. The difference in global lumbar L1-S1 lordosis was –2.9°. Analysis of the Roussouly groups showed the largest difference for L1-S1 (–8.3°) in group 2. In group 4, when measured on MRI, L5 / S1 lordosis (25.71°) was lower than L4 / L5 lordosis (27.63°) compared to the other groups.Conclusions Although measurements of global lumbar lordosis significantly differed between the two scanning technologies, the mean difference was just 2.9°. MRI in supine position may be used for estimating global lumbar lordosis, but single level lordosis should be determined by means of standing radiographs.Key Points Citation Format
Keywords: lumbar lordosis; sagittal balance; standing radiographs; supine MRI; sacral slope; lumbar spine